(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Spiders (Araneae) are the ablest predators to settle in the larval nests of Hyphantria cunea Drury (Lepidoptera Arctiidae). In the summer of 1992 a relevant research was carried out on the presence of and the possible role played by these predators in the nests infesting Morus alba L. in the central Po Valley. Spiders belonging to at least 10 species were present in 21.4 per cent of the 163 nests of Fall Webworm gathered in 8 localities of the Po Valley. Various parameters were considered, such as the dimensions of the larvae preyed on by the Spiders, the different biotopes occupied by Morus alba L., the characteristics of some of the Spiders species. A first summary of the situation is given in regard to the actual and anything but negligible role of the predators as natural enemies of this infesting moth in Italy.